Welfare Regimes in the UE 15 and in the Enlarged Europe - an Exploratory Analysis - Leonor Vasconcelos Ferreira; Adelaide Figueiredo (European Regional Science Association (ERSA), 2005)
The basic aim of this paper is to assess existing welfare regimes in the countries of European Union before and after the enlargement of May 2004 (EU 15 and EU 25) following a comprehensive approach that considers different dimensions of welfare through an extended set of variables. The paper starts with a brief presentation of current debates on welfare regimes and the new social policy agenda in the European Union. It proceeds with the selection of different dimensions of social welfare and social policy, and related key variables that constitute the database for the following statistical analysis. Correlations, factor analysis and cluster analysis are performed in order to produce the clustering of welfare regimes as well as a tentative interpretation of underlying characteristics and patterns of welfare mix and social policies in European Union.
Keywords: 330